School-based screening to identify children at risk for attention-deficit/hyperactivity disorder: Barriers and implications. Issue 3 (2nd July 2016) - Barry, Tammy D.; Sturner, Raymond; Seymour, Karen; Howard, Barbara; McGoron, Lucy; Bergmann, Paul; Kent, Ronald; Sullivan, Casey; Tomeny, Theodore S.; Pierce, Jessica S.; Coln, Kristen L.; Goodlad, James K.; et al.
ABSTRACT: This report describes a school-based screening project to improve early identification of children at risk for attention-deficit/hyperactivity disorder (ADHD) and communicate these concerns to parents, recommending that they contact their child's primary care provider (PCP). Of 17, 440 eligible children in first through fifth grades in five school districts, 47.0% of parents provided required written consent, and teachers completed 70.4% of the online screeners (using the Vanderbilt AD/HD Diagnostic Teacher Rating Scale). Of 5, 772 screeners completed, 18.1% of children ( n = 1, 044) were identified as at risk. Parents of at-risk children were contacted to explain risk status and recommended to visit their child's PCP for further evaluation. It was not possible to contact 39.1% of parents of at-risk children. Of the 636 parents of at-risk children who could be contacted, 53.1% ( n = 338) verbally accepted the recommendation to follow-up with their PCP, which was not related to ADHD symptom severity. Parents of children with IEPs or related services were more likely to accept the recommendation to visit the PCP. Our exploration of the potential for school-based screening for ADHD identified a number of barriers to successful execution, but the data also indicated that this is an important problem to address.